A study on the economic potential of blood cockles (Anadara granosa) in Rokan Hilir, Riau Province, Indonesia - Yulinda, Eni; Saad, Mazni; Yusuf, Muhammad (2020)
This research was conducted from January to July 2019 in Rokan Hilir Regency, Riau Province for the purpose of investigating the prospects and economic potentials of blood cockle (Anadara granosa) cultivation in the regency. The methods used included a survey, direct observation and an in-depth interview with 65 marine cockle cultivators and related stakeholders in the three production centers of marine fisheries, namely Panipahan, Bagansiapiapi and Sinaboi. The data obtained were analyzed descriptively and its business feasibility analyzed. The results showed that the blood cockle cultivation business of Rokan Hilir is very profitable (BCR 1.88 and PPC 1.92). In addition, the prospects of developing cockle cultivation is also good because of the wide (124,000,000 m2) land potential available, the low demand for high skills, and the accessibility for export of products to the Malaysian market.